Prinsip Regulatory Impact Assessment dalam Proses Penyusunan Peraturan Perundang-Undangan Sesuai UU Nomor 12 Tahun 2011 - Suska, Suska (Mahkamah Konstitusi Republik Indonesia, 2012)
Regulatory impact assessment (RIA) is a method of policy development with an approach that accommodate all requirements in regulatory process. This method improved rapidly in early 2000 and used widely in OECD countries. Regulatory framework in Indonesia is regulated in Law number 12 Year 2011 about the Making of Law assigned the process of lawmaking. This research compares the RIA’s concept with the process in Law number 12 . The result of the research shows there are some processes in RIA which are not covered by the process in the Law particularly about the coverage of all possible alternatives in the regulation including the benefit and cost analysis for each alternative and also monitoring mechanism to evaluate the effectiveness of the policy and recommend improvement for future regulation